Role of age-related plasma in the diversity of gut bacteria - Ceylani, Taha; Allahverdi, Huseyin; Teker, Hikmet Taner (Elsevier Ireland Ltd, 2023)
Recent studies have demonstrated the efficacy of young blood plasma factors in reversing aging-related de-formities. However, the impact of plasma exchange between young and old individuals on gut microbiota re-mains understudied. To investigate this, we evaluated the effects of plasma exchange between 5-week-old and 24-month-old rats on gut microbiota composition. In this study, old rats were administered 0.5 ml of young plasma, while young rats were administered 0.25 ml of old plasma daily for 30 days. Metagenome analysis was performed on the contents of the cecum after completing plasma transfer. Results showed that transferring young plasma to old rats significantly increased the alpha diversity indices (Shannon and Simpson values), while the Firmicutes to Bacteroidetes ratio decreased significantly. Conversely, transferring aged plasma to young rats led to a significant decrease in Shannon value and F/B ratio but no change in Simpson value. Plasma exchange also caused substantial changes in the top ten dominant genera and species found in the gut microbiota of young and old rats. After young blood plasma transfer, the dominant bacterial profile in the old gut microbiota shifted toward the bacterial profile found in the young control group. Notably, old plasma also altered the gut micro -biota structure of young rats toward that of old rats. Our findings suggest that age-related changes in plasma play a crucial role in gut microbiota species diversity and their presence rates.
Keywords: Aging; Plasma Exchange; Gut Microbiota; Metagenome; Alpha Diversity; Sprague Dawley Rat; Young Blood; Microbiota; Rejuvenation; Rats